Reflection of English Language Teaching for High School Students Using E-LISDA E-Learning Platform - Hasbi, Muhamad; Purnama, Restu (Cipta Pustaka Nusantara, 2024)
This study aims to describe the implementation of E-LISDA e-learning platform in English language teaching and the teachers’ challenges in using it in English language teaching at SMA Islam Sudirman Ambarawa. Two English teachers from SMA Islam Sudirman Ambarawa served as the study's subjects. Researchers used a descriptive qualitative approach to gather data through observation, documentation, and interviews. The results showed that teachers used E-LISDA to manage online learning sessions such as in the forms of sharing English materials, conducting distant classroom activities, exchanging information, and motivating students, where they have followed four out of Salmon’s five required e-learning stages, namely access and motivation, information exchange, knowledge construction, and development; the online socializing stage was absent. In using E-LISDA, teachers faced several challenges, such as unstable internet networks, electricity cuts, students’ low academic performances, and students’ practice of cheating.